Electricity costs in irrigated agriculture: A case study for an irrigation scheme in Spain. (February 2017) - Langarita, Raquel; Sánchez Chóliz, Julio; Sarasa, Cristina; Duarte, Rosa; Jiménez, Sofía
Abstract: Electricity prices have risen sharply in Spain in recent years, to the point where they are now among the highest in the EU. The scant competition between power utilities, changes in the law, and the tariff deficit (accumulated debt in favour, mainly, of the electricity firms), have driven up the cost of electricity, affecting numerous other industries such as irrigated agriculture, a sector that has significantly increased its electricity consumption as a result of modernization processes over the past twenty-five years. We examine these issues through a case study of an irrigation scheme in Spain that provides irrigation water and infrastructure to 58 farming communities in north-eastern Spain, and is highly representative of the Ebro Valley. Based on the results of direct estimations and simulations of different tariffs, we propose the lowering of capacity-based tariffs to reduce sector problems and cut energy costs, especially for farmers. We also raise the possibility of increasing self-consumption, a complementary measure for many farmers and for medium-size firms.